¿Does the incorporation of different species of Lupinus as green manure, affects the microbial activity of the soil? - Zapata Hernández, Isidro; Zamora Natera, Juan Francisco; Trujillo Tapia, Ma Nieves; Ramirez Fuentes, Eustacio (REVISTA TERRA LATINOAMERICANA, 2020)
In the state of Jalisco, corn and tequila agave are the most important agricultural crops. The soils to cultivate these species are characterized by low content of organic matter and nitrogen. The amendments applied to the soil provide an important source of energy and nutrients for microorganisms; promotes the diversity of nitrogen-f ixing bacteria and nitrifying bacteria, which increases nitrogen availability in the soil. The aim of this study was to evaluate the use of two species of wild legumes: Lupinus exaltatus and Lupinus rotundiflorus as green manure (AV), and its effect on soil microbial biomass. An aerobic incubation experiment (14 days) was carried out on soil samples with green manure and without green manure (control). Under laboratory conditions, the microbial activity of soil was monitored through the response in basal respiration and the concentration of C and N in the microbial biomass. The CO2 production and C and N content in the microbial biomass showed significant differences (P < 0.05) due to the effect of green manure. The residues of Lupinus are considered better quality than the residues of Zea mays due to its nitrogen content and low C: N ratio. The response of microorganisms presented a positive primer effect with the input of AV. Therefore, we conclude that the input of L. exaltatus and L. rotundiflorus as a green manure to the soil increases the biological activity of the soil and promotes the enrichment of C and N of the microbial biomass.